Jangan Berikan Kepadaku Kemiskinan atau Kekayaan - Bertha Wandasari Sinukaban (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
This paper examines the meaning of Agur the son of Jakeh's prayer in Proverbs 30:7-9 as a text that offers simple life. This research uses qualitative methods with interpretation-design of wisdom literature which analyzes text, structure, and sentence form. This research finds that Proverbs 30:7-9 reflects simple life which is very relevant to apply in today's life. Simple life is a simple way of life that is appropriate to prevent consumerism, hedonism, and greed. This finding can be seen in Agur the son of Jakeh's request for a 'middle state' (neither poor nor rich) and the motivation for life that is echoed in his prayer. This research is an input and reminder for every believer and church to live their simple life by Biblical values as a form of gratitude, trust, and loyalty to God.